2011
DOI: 10.1523/jneurosci.2516-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Caltubin, a Novel Molluscan Tubulin-Interacting Protein, Promotes Axonal Growth and Attenuates Axonal Degeneration of Rodent Neurons

Abstract: Axotomized central neurons of most invertebrate species demonstrate a strong regenerative capacity, and as such may provide valuable molecular insights and new tools to promote axonal regeneration in injured mammalian neurons. In this study, we identified a novel molluscan protein, caltubin, ubiquitously expressed in central neurons of Lymnaea stagnalis and locally synthesized in regenerating neurites. Reduction of caltubin levels by gene silencing inhibits the outgrowth and regenerative ability of adult Lymna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Colocalization of fluorescent signals suggests a high probability of two antigens cooccurring in close proximity, indicated by Pearson’s correlation coefficient (Rr; one signifies a high degree of colocalization, and zero indicates low likelihood of localization) [26]. The colocalization of TRPM7 and α-actinin-1 or F-actin was focused within the lamellipodia (mesh-like structures) and filopodia (filamentous structures) of the neuronal growth cones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colocalization of fluorescent signals suggests a high probability of two antigens cooccurring in close proximity, indicated by Pearson’s correlation coefficient (Rr; one signifies a high degree of colocalization, and zero indicates low likelihood of localization) [26]. The colocalization of TRPM7 and α-actinin-1 or F-actin was focused within the lamellipodia (mesh-like structures) and filopodia (filamentous structures) of the neuronal growth cones.…”
Section: Resultsmentioning
confidence: 99%
“…Images of neurons were captured with either a Leica TCS LS confocal laser-scanning microscope (Heidelberg, Germany; Leica confocal software, version 2.5; build 1347; Leica Microsystems) with either ×40 (NA 1.25) or ×63 (NA 1.32) oil immersion lenses, and 488-, 543-, and 633-nm lasers, as described previously [26], or a Carl Zeiss confocal laser scanning microscope LSM700 with either ×63 DIC (NA 1.40) or ×40 DIC (NA 1.3) oil immersion lenses, and 405-, 488-, and 543-nm lasers [4]. Each Z -plane was 0.3 μm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium is a ubiquitous second messenger and is important in the control of neuronal migration and neurite development (Komuro and Kumada, 2005; Zheng and Poo, 2007). Studies have shown that EF-hand proteins such as MACF1, caltubin, and calmyrin1 regulate cytoskeletal components through EF-hand motifs during neurite outgrowth (Nejatbakhsh et al, 2011; Sanchez-Soriano et al, 2009; Sobczak et al, 2011), suggesting potential roles of EF-hand motif in MACF1 activity during neuronal development. Future studies would address whether the actin-microtubule bridging property of MACF1 is dependent on calcium binding in the EF-hand motif.…”
Section: Discussionmentioning
confidence: 99%
“…In order to eliminate synaptic inputs from the periphery to the RPeD1, isolated preparations of the central ring ganglia were dissected as described previously (Elliott and Benjamin, 1989; Feng et al, 2009; Nejatbakhsh et al, 2011). The central ring ganglia and buccal ganglia were isolated from the body and pinned dorsal side up on a dissecting board filled with snail saline.…”
Section: Methodsmentioning
confidence: 99%